Research progress of steel slag-based carbon sequestration - Qing Zhao; Chengjun Liu; Xiaohui Mei; Henrik Saxén; Ron Zevenhoven (Fundamental Research)
Large amounts of steel slag (SS) and CO2 are produced globally each year during steel production. An SS-based carbon capture and utilization (SS-CCU) process for CO2 mineralization is suitable specifically for steel-making industries for simultaneous mitigation of CO2 emissions and valorization of wastes. However, the SS-CCU process is currently in the stage of laboratory research and far away from industrial application. In this review, some SS-CCU processes, including direct and indirect carbonation processes, were explored and summarized. Herein, the key factors and mechanisms of the SS-based CO2 sequestration process were identified. The carbonation process efficacy and its environmental impact (including global warming, energy use, water use, and metallic pollutants) were evaluated. Furthermore, the challenges and prospects of the further development of the SS-CCU process were discussed.